2022
DOI: 10.1007/s00044-022-02918-7
|View full text |Cite
|
Sign up to set email alerts
|

The mechanism of resistance in Escherichia coli to ridinilazole and other antibacterial head-to-head bis-benzimidazole compounds

Abstract: The appY gene has been characterised as conferring resistance to a novel series of antimicrobial benzimidazole derivatives in E. coli MC1061 cells when expressed in high copy-number. A microarray approach was used to identify genes involved in the mechanism of appY-mediated antibacterial resistance, that were up- or down-regulated following induction of the gene in the appY knockout strain JW0553. In total, expression of 90 genes was induced and 48 repressed greater than 2.5-fold (P < 0.05), 45 min after ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 49 publications
1
1
0
Order By: Relevance
“…5A ), returning MICs lower than the values observed against C. difficile , while the wild-type BW25113 parental strain was not susceptible. These data complement recent observations that overexpression of an efflux pump ( mdtEF ) restored ridinilazole resistance to a permeable E. coli strain ( 18 ). We also demonstrated that the enhanced fluorescence of ridinilazole upon DNA binding in vitro was apparent, and comparable when using either E. coli or C. difficile genomic DNA ( Fig.…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…5A ), returning MICs lower than the values observed against C. difficile , while the wild-type BW25113 parental strain was not susceptible. These data complement recent observations that overexpression of an efflux pump ( mdtEF ) restored ridinilazole resistance to a permeable E. coli strain ( 18 ). We also demonstrated that the enhanced fluorescence of ridinilazole upon DNA binding in vitro was apparent, and comparable when using either E. coli or C. difficile genomic DNA ( Fig.…”
Section: Resultssupporting
confidence: 89%
“…Of the top 60 upregulated genes, eight comprise the entirety of the glycine reductase operon ( grdX , trxB3 , trxA2 , grdEABCD ) (Table S1) ( 17 ). Glycine reductase is a key enzyme in the Stickland pathway which couples the oxidation and reduction of amino acid pairs to the formation of ATP and is the major anaerobic mechanism by which C. difficile generates energy ( 18 ). The most efficient Stickland electron acceptors are glycine, proline and hydroxyproline ( 17 ) and we observed that genes in the proline reductase operon were among the most downregulated genes ( prdABDE prdE2 prdF ).…”
Section: Resultsmentioning
confidence: 99%